2022
DOI: 10.1088/1361-6463/ac6239
|View full text |Cite
|
Sign up to set email alerts
|

Acetylammonium chloride as an additive for crystallization control and defect passivation in MAPbI3 based perovskite solar cells

Abstract: Uniform and high-electronic-quality perovskite thin films are necessary for high efficiency perovskite solar cells (PSCs) and additives play a major role in improving the quality of the perovskite films. Here, we demonstrate acetylammonium chloride (AAC) as an additive to effectively control the morphology and crystal quality of the methylammonium lead iodide perovskite film. AAC incorporated PSCs have shown an improved power conversion efficiency (PCE) of 15.9% compared to 14.9% of the control device. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…In addition, the performance of PSCs is significantly influenced by the characteristics of the interface layers. It is widely speculated that low-quality interfaces result in larger surface/interface defect densities, which in turn increase the recombination of charge-carriers [ 74 ]. We assume that the defect densities of IDL1 and IDL2 range between 10 18 and 10 22 cm −3 in order to discuss the impact of the defect density of the interface layers on the PSC performance.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the performance of PSCs is significantly influenced by the characteristics of the interface layers. It is widely speculated that low-quality interfaces result in larger surface/interface defect densities, which in turn increase the recombination of charge-carriers [ 74 ]. We assume that the defect densities of IDL1 and IDL2 range between 10 18 and 10 22 cm −3 in order to discuss the impact of the defect density of the interface layers on the PSC performance.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous initiatives have been made to address the aforementioned issues, including interfacial, compositional, device structure, crystallization, and additive engineering. Introduction of additives into the perovskite precursor solution can help in controlling the crystal growth of perovskite films and the passivation of defects. Additives that mix with precursors have been shown to effectively delay the crystallization process and, as a result, enhance homogeneous nucleation and crystallization kinetics. Zou et al have reported the underlying relationship among crystallization dynamics, charge carrier kinetics, device performance, and device operational stability under ambient conditions with the introduction of ionic liquid additives, which can control the crystal growth.…”
Section: Introductionmentioning
confidence: 99%
“…The deep level defects that are present in the perovskite bulk and surface act as recombination centers for charge carriers, which results in the reduced open-circuit voltage ( V OC ) of the PSCs. Effective passivation of these defects can be achieved by the addition of Lewis base or acids, ionic liquids, quantum dots, fullerene derivatives, and inorganic salts, which can annihilate defect-induced charge traps. ,, Prior research has shown that carbonyl groups possessing lone pair electrons act as Lewis bases and demonstrate robust passivation capabilities by forming coordination bonds with under-coordinated lead ions. , Also, it is reported that amino groups can form hydrogen bonds with interstitial iodine. , Additives described in the literature typically have one or two functional groups that aid in defect passivation. Other parts of the additive are inactive and have no interactions with the perovskite layer.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The progress is due to various improvements in the processing of perovskite films (PFs) and a better understanding of its transport properties, bandgap tuning, absorption coefficient, and crystallization properties. [3][4][5][6][7][8][9][10][11] The high-performance PSCs are usually made with lead (Pb) as its B content in its ABX 3 structure, where A can be methylammonium (MA), formamidinium (FA), cesium (Cs), or mixed cations, and X can be chlorine (Cl), bromine (Br), and iodine (I) or a combination. [12][13][14] The performance and stability of the PSCs majorly depend on the PF quality and its contents.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] PFs are prepared by two-step or single-step spin-coating methods. [11,17] Perovskite crystal growth leading to good quality PFs depends on thermodynamic conditions, solvent properties, and environmental conditions such as humidity, temperature, etc. Even though the precursor solutions are prepared in stoichiometric ratios, inadvertently, most of the PFs are formed with excess or less lead iodide (PbI 2 ).…”
Section: Introductionmentioning
confidence: 99%